A taxonomic review of the genus Ephysteris Meyrick, 1908 (Lepidoptera, Gelechiidae) in the Afrotropical region - Bidzilya, Oleksiy V.; Rajaei, Hossein (Zootaxa, 2026)
The genus Ephysteris in the Afrotropical region is revised. Eighteen species are recognized as valid, six of which are described as new: E. crypticus sp. nov. (Kenya), E. afrorientellus sp. nov. (Kenya, Ethiopia), E. minutus sp. nov. (South Africa, Namibia), E. griseellus sp. nov. (South Africa), E. permanus sp. nov. (South Africa), E. jansei sp. nov. (South Africa). Additionally, the following new synonymies are established: Microcraspedus brachypogon (Meyrick, 1937) and Gnorimoschema infirma Meyrick, 1912, both syn. nov. of Ephysteris sirota (Meyrick, 1908); Scrobipalpa sibila (Meyrick, 1921) syn. nov. of Ephysteris cretigena (Meyrick, 1914); Ephysteris parasynecta Janse, 1963 syn. nov. of Neotelphusa anisogrisea Janse, 1958; Ephysteris fuscocrossa Janse, 1961 syn. nov. of Sitotroga psacasta (Meyrick, 1908); Ephysteris neosirota (Janse, 1950) syn. nov. of Ephysteris obstans (Meyrick, 1928) comb. nov. (Scythris). Moreover, Ephysteris photinopa (Meyrick, 1920) is combined to Photodotis Meyrick, 1911: Photodotis photinopa (Meyrick, 1920) comb. nov. Beside these taxonomic changes, Ephysteris promptella is recorded for the first time from DR Congo, Cameroon, Kenya, Tanzania and Seychelles; E. arabiae is new for Yemen; E. sirota is new for Kenya, E. iberica is new for South Africa and Kenya, and E. leptocentra is new for Zambia. Lectotypes are designated for Phthorimaea sibila Meyrick, 1921 and Gnorimoschema infirma Meyrick, 1912. All species are diagnosed, and genitalia are redescribed based on additional material. Identification keys and photographs of adults and genitalia are provided.